Non-invasive recording of His bundle potential in man. Simplified method. - Hishimoto, Y (1975)
In 6 cases with sinus rhythm and one with atrial fibrillation, the bipolar surface electrocardiograms were taken through band pass filters simultaneously with the intracavitary His bundle electrogram, and averaged using a signal processer. By these relatively simplified procedures 'blips' considered to be derived from His bundle potentials between PR segments could be recorded. It was found that 'blips' originating from the His bundle were recorded most distinctly when a cathode was applied to the posterior mid-line and an anode to the sternum, both at the level of the fourth intercostal space. In some instances it was possible to record 'blips' probably derived from the bundle-branches. To identify the onset of ventricular potentials it was necessary to refer to the surface electrocardiograms taken with a usual time constant. The interval from the onset of 'blip' to the onset of ventricular activity (BV) agreed perfectly with the directly recorded His bundle to ventricle conduction time (HV) in 6 out of 7 cases investigated, and in the remaining case this interval was found to be only 1 ms longer than the HV.